2018
DOI: 10.1016/j.cell.2018.03.076
|View full text |Cite
|
Sign up to set email alerts
|

GPR68 Senses Flow and Is Essential for Vascular Physiology

Abstract: Mechanotransduction plays a crucial role in vascular biology. One example of this is the local regulation of vascular resistance via flow-mediated dilation (FMD). Impairment of this process is a hallmark of endothelial dysfunction and a precursor to a wide array of vascular diseases, such as hypertension and atherosclerosis. Yet the molecules responsible for sensing flow (shear stress) within endothelial cells remain largely unknown. We designed a 384-well screening system that applies shear stress on cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(244 citation statements)
references
References 61 publications
10
219
1
Order By: Relevance
“…The reason for this selection is because we found that dilation responses were relatively consistent across arteries of slightly different diameters and magnitudes of preconstriction at each flow rate (Fig. 1), and these response curves were similar to those found in many previous studies using stepped increases in flow in mouse mesenteric arteries (Loufrani et al 2002;Ohlmann et al 2005;Sennoun et al 2009;Priou et al 2010;Leonetti et al 2013;Tarjus et al 2017;Xu et al 2018), and more robust than found in some studies (Douglas et al 2008;Besnier et al 2018). Although the calculated shear stress was different between arteries at the start of flow (Initial Shear Stress), due to variation in diameters after preconstriction with phenylephrine, the final calculated shear stress (Final Shear Stress) values had much less variability as indicated by the smaller SEM ("Control" arteries in Tables 2 and 3).…”
Section: Limitationssupporting
confidence: 84%
See 1 more Smart Citation
“…The reason for this selection is because we found that dilation responses were relatively consistent across arteries of slightly different diameters and magnitudes of preconstriction at each flow rate (Fig. 1), and these response curves were similar to those found in many previous studies using stepped increases in flow in mouse mesenteric arteries (Loufrani et al 2002;Ohlmann et al 2005;Sennoun et al 2009;Priou et al 2010;Leonetti et al 2013;Tarjus et al 2017;Xu et al 2018), and more robust than found in some studies (Douglas et al 2008;Besnier et al 2018). Although the calculated shear stress was different between arteries at the start of flow (Initial Shear Stress), due to variation in diameters after preconstriction with phenylephrine, the final calculated shear stress (Final Shear Stress) values had much less variability as indicated by the smaller SEM ("Control" arteries in Tables 2 and 3).…”
Section: Limitationssupporting
confidence: 84%
“…1A in [Looft-Wilson et al 2008]) and the deep constriction allows observation of a larger magnitude flow-induced vasodilation response. Moreover, use of this agonist and this magnitude of preconstriction is typical when examining flow-induced dilation in these arteries (Loufrani et al 2002;Sennoun et al 2009;Tarjus et al 2017;Besnier et al 2018;Xu et al 2018). This phenylephrine dose results in eNOS phosphorylation changes (Looft-Wilson et al 2013), and it is possible that these phosphorylation changes are maximal.…”
Section: Limitationsmentioning
confidence: 99%
“…We examined expression of GPCR along the aligned trajectories. The vasodilatory flow sensor gene Gpr68 59 first arises in pre-Art capillary EC and is retained in Art ( Fig. 7c ).…”
Section: Resultsmentioning
confidence: 99%
“…In Xenopus, v-atpase regulates pH in a regional manner to affect craniofacial morphogenesis (Adams et al, 2006;Vandenberg et al, 2011) . Notably, recent studies of GPR68 have shown that the receptor senses flow and stretch (Wei et al, 2018;Xu et al, 2018) . However, responses to both stimuli are dependent on mildly acidic conditions.…”
Section: Discussionmentioning
confidence: 99%